Reliability analysis of underground tunnel: an overview - Thapa, Axay; Roy, Atin; Chakraborty, Subrata (Journal of Structural Engineering, 2024)
Probabilistic analysis of underground tunnels is getting increasing importance as the approach can explicitly considerinherent uncertainties in the involved parameters to provide a rational perspective in the analysis and design ofunderground tunnel structures. In fact, reliability analysis of underground tunnels is an active field of research inrecent years. Like reliability analysis of any other structure, the developments in tunnel reliability analysis approacheshave also taken place under two sub-heads i.e. analytical and simulation-based approaches. Noting the difficulty ofperforming reliability analysis by those approaches for real-life tunnels that involves evaluation of implicit nonlinearperformance functions by tiring finite element simulation, the metamodel-based reliability analysis approach hasbeen widely applied in tunnel reliability analysis. The present article provides an overview of related developmentsin analytical and simulation-based tunnel reliability analysis with special emphasis on the application of variousmetamodeling approaches in such analysis. Based on the overview of the developments in tunnel reliability analysispresented here, the challenges and opportunities in the field are summarized. The article is likely to augment the stateof-the-art developments of tunnel reliability analysis.